Pathophysiology of atherosclerosis: Association of risk factors and treatment strategies using plant‐based bioactive compounds. Issue 11 (27th August 2020) - Sharif, Hina; Akash, Muhammad Sajid Hamid; Rehman, Kanwal; Irshad, Kanwal; Imran, Imran
Abstract: Under physiological conditions, endothelial cells act as protective barrier which prevents direct contact of blood with circulating factors via production of tissue plasminogen activator. Risk factors of metabolic disorders are responsible to induce endothelial dysfunction and may consequently lead to prognosis of atherosclerosis. This article summarizes the process of atherosclerosis which involves number of sequences including formation and interaction of AGE‐RAGE, activation of polyol pathway, protein kinase C, and hexosamine‐mediated pathway. All these mechanisms can lead to the development of oxidative stress which may further aggravate condition. Different pharmacological interventions are being used to treat atherosclerosis, however, these might be associated with mild to severe side effects. Therefore, plant‐based bioactive compounds having potential to combat and prevent atherosclerosis in diabetic patients are attaining recent focus. By understanding process of development and mechanisms involved in atherosclerotic plaque formation, these bioactive compounds can be better option for future therapeutic interventions for atherosclerosis treatment. Practical applications: Atherosclerosis is one of major underlying disorders of cardiovascular diseases which occur through multiple mechanisms and is associated with metabolic disorders. Conventional therapeutic interventions are not only used to treat atherosclerosis, but are also commonly associated with mild to severe side effects. Therefore, nowadays, bioactive compounds having potential to combat and prevent atherosclerosis in diabetic patients are preferred. By understanding mechanisms involved in atherosclerotic plaque formation, bioactive compounds can be better understood for treatment of atherosclerosis. In this manuscript, we have focused on treatment strategies of atherosclerosis using bioactive compounds notably alkaloids and flavonoids having diverse pharmacological and therapeutic potentials with special focus on the mechanism of action of these bioactive compounds suitable for treatment of atherosclerosis. This manuscript will provide the scientific insights of bioactive compounds to researchers who are working in the area of drug discovery and development to control pathogenesis and development of atherosclerosis and its associated cardiometabolic disorders. Abstract : Hyperglycemia is major risk factor of formation of AGEs which can react with its receptor RAGE and causes the activation of NF‐κB. All this can lead to diabetic vascular complications. Risk factors of metabolic disorders are responsible to induce endothelial dysfunction and consequently lead to the prognosis of atherosclerosis. By understanding the mechanisms involved in atherosclerotic plaque formation, bioactive compounds can be better understood for treatment of atherosclerosis.